Implementasi Metode Ripple Down Rules (RDR) dan Metode Certainty Factor Pada Sistem Pakar Diagnosa Pompholyx - Darman Jaya Laia (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2020)
Pompholyx is a skin disease characterized by the appearance of small, fluid-filled blisters, especially on the sides of the fingers, palms, and soles of the feet. In general, the blisters last three weeks, and produce severe itching and burning. The blisters can also be accompanied by pain and drain pus. Pompholyx is also known as dyshidrotic eczema. If not treated properly, people with pompholyx can develop bacterial infections, as a result of scratching the affected area of the skin. Therefore, a tool that is able to provide real and accurate diagnostic information based on the symptoms that occur in sufferers of this disease is needed, namely an expert system application. Expert system applications can work properly according to expert knowledge to diagnose diseases that are experienced based on the symptoms that arise. The expert system for diagnosingdisease Pompholyx in this study the authors design and build with vbnet 2008. The method applied to the expert system in this study is the Ripple Down Rules (RDR) Method and the Certainty Factor Method. The knowledge base for diagnosing Pompholyx was obtained from expert doctors to diagnose this disease, namely specialists at Herna General Hospital. The results of this study are in the form of an expert system which is expected to contribute to helping many people more easily get diagnosis information fordisease Pompholyx easily.Keywords: Expert System, Diagnosis, Pompholyx, Ripple Down Rules (RDR), Certainty